Fleksibilitas Asynchronous Learning Berbasis Android sebagai Inovasi Pembelajaran Pendidikan Agama Islam di Sekolah Menengah Pertama - Farikhin Farikhin; Asep Saepul Hamdani; Irma Soraya (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2022)
The COVID-19 pandemic, for the past two years, has significantly impacted the world of education. Educational institutions carry out various innovations in the learning process. Innovations in this learning model can still be applied in normal times, such as face-to-face learning. This study uses a qualitative approach to determine the android-based asynchronous learning model in Islamic religious education (PAI) learning at Nurul Anwar Islamic Middle School Pasuruan. Data collection techniques using interviews with subject teachers and students and observation. The study results explain that asynchronous learning based on android WhatsApp at Islamic Junior High School (SMP Islam) Nurul Anwar Pasuruan can be appropriately implemented because it is supported by each student's gadget facilities and positive responses to student activity during the learning process. Asynchronous learning as an optional supplement and a complement to face-to-face learning help PAI teachers distribute materials or assignments that students can access through their respective gadgets and WhatsApp applications. Teachers feel that with this asynchronous learning, PAI learning becomes more effective.